Determination of damping ratio using Monte-Carlo method. Issue 1 (January 2021) - Peng, Q; Ding, Y; Huang, Y; Zhu, Z
Abstract: This paper highlights an innovant method for calculating the damping ratio using Monte-Carlo method. Compared with other approaches reported in the literature, the clear benefit of the method is the ability to directly determinate the damping ratio upon irregular stress-stain curves through Python. By using Monte-Carlo method, it is found that (i) the computed damping ratios are consistent with the undrained cyclic triaxial result on a dense reference sand specimen; (ii) while total random samplings number for each hysteresis loop greater than 5000 times, the method could provide a satisfactory analysis.